Functional status of the cardiovascular system in the wounded with limb injuries at the levels of health care according to tetrapolar rheography - I. P. Khomenko; S. O. Korol; A. A. Kozhokaru; B. V. Matviichuk; R. M. Sichinava (Zaporozhye State Medical University, 2019)
The degree of irreversible pathophysiological changes in traumatic shock has no early clinical manifestations, since in 16.7 % of cases the anatomical assessment of the severity of the injury and the severity of the condition of the injured is determined, which is related to the peculiarity of the body compensatory capacity, timeliness and quality of quality of anti-shock measures. The aim of the work is to conduct, on the basis of clinical and statistical analysis of changes in the indicators of functional disorders of the cardiovascular system, a pathophysiological justification of the general condition of the wounded with combat trauma of the extremities at the levels of medical support. Materials and methods. An array of studies consisted of 378 wounded with combat injuries to their extremities. Pathophysiological assessment of homeostasis in the comparison groups was performed according to 14 indicators determined immediately after the admission of the wounded to the anti shock ward by the method of tetrapolar rheography. The Admission trauma scale (AdTS) was used to assess the severity of the injuries. Results. In the wounded with severe and extremely severe trauma, starting from the second level of medical support, during the sequential implementation of countermeasures during the stages of medical evacuation, there was a positive dynamics of changes in the indicators of the cardiovascular system status to a mild degree. With the reduction of stages, there was a tendency to deterioration of the general condition of the wounded and decrease of indicators by 41.8-53.6 % to irreversible values (Pα < 0.05). Dynamic changes in the severity of functional disorders of the cardiovascular system confirmed the benefits of a sequential evacuation scheme for the wounded with severe and extremely severe injuries. In patients with mild trauma, reducing the levels did not worsen the general condition, and functional disorders were moderate. Conclusions. Consistent providing of traumatological care to the wounded at the levels of medical support, due to timely performed surgical interventions, carrying out countermeasures and maintaining the reserve forces of the body of the wounded with extremely severe and severe combat injuries of the extremities (5 points or more) allows to achieve a gradual change of the functional state of the cardiovascular system from severe to moderate. Assistance to the injured with a minor trauma (<5 points) under the reduced scheme does not lead to a decrease in functional indicators.